Analisis Alternatif Kebijakan Pengembangan Ekowisata Desa Pinang Banjar Berbasis Sinergi antar Stakeholder - Berliana Safitri, Aisyah; Junaidi, Junaidi; Dwi Permata Sari, Intan; Aini, Syarifah; Keril, Radia; Sen You, Taufal (PUBLICNESS: Journal of Public Administration Studies, 2026)
This study aims to analyze policy alternatives for the development of ecotourism in Pinang Banjar Village, Gelumbang District, Muara Enim Regency, by emphasizing the importance of stakeholder synergy as the foundation for policy implementation. The research focuses on identifying key problems and formulating the most feasible and implementable policy alternatives, particularly in addressing infrastructure limitations and the condition of policy vacuum, defined as the absence of specific policies at the regency level and the lack of integration of ecotourism development into regional planning documents such as the RPJMD and RIPPARD. This study employs a comprehensive policy analysis approach using the Patton and Sawicki model. Data were collected through observation, interviews, and documentation involving three key informants, namely local ecotourism managers. The analysis was conducted based on the criteria of effectiveness, efficiency, equity, political feasibility, and administrative sustainability. The findings indicate that weak stakeholder synergy is the primary factor hindering ecotourism development. This condition affects limited budget support, the absence of formal management institutions, low community capacity, and the lack of integration of ecotourism into regional development planning. These findings suggest that partial policy alternatives are insufficiently effective. Therefore, the most feasible policy alternative is an integrative approach that combines strengthening basic infrastructure, community empowerment through the establishment of Tourism Awareness Groups (Pokdarwis), enhancement of digital promotion, and integration of regional policies with improved stakeholder synergy. This recommendation is expected to serve as a reference for promoting inclusive and sustainable ecotourism development.